Generation of hematopoietic cells from mouse pluripotent stem cells in a 3D culture system of self‐assembling peptide hydrogel. Issue 3 (6th August 2019) - Shan, Wei; Wang, Binsheng; Xu, Yulin; Li, Xia; Li, Xue; Wang, Huafang; Lin, Yu; Tie, Ruxiu; Zhao, Qianhao; Wang, Jinyong; Zheng, Weiyan; Hu, Yongxian; et al.
Abstract: In vitro generation of hematopoietic stem cells from pluripotent stem cells (PSCs) can be regarded as novel therapeutic approaches for replacing bone marrow transplantation without immune rejection or graft versus host disease. To date, many different approaches have been evaluated in terms of directing PSCs toward different hematopoietic cell types, yet, low efficiency and no function restrict the further hematopoietic differentiation study, our research aims to develop a three dimension (3D) hematopoietic differentiation approach that serves as recapitulation of embryonic development in vitro to a degree of complexity not achievable in a two dimension culture system. We first found that mouse PSCs could be efficiently induced to hematopoietic differentiation with an expression of hematopoietic makers, such as c‐kit, CD41, and CD45 within self‐assembling peptide hydrogel. Colony‐forming cells assay results suggested mouse PSCs (mPSCs) could be differentiated into multipotential progenitor cells and 3D induction system derived hematopoietic colonies owned potential of differentiating into lymphocyte cells. In addition, in vivo animal transplantation experiment showed that mPSCs (CD45.2) could be embedded into nonobese diabetic/severe combined immunodeficiency mice (CD45.1) with about 3% engraftment efficiency after 3 weeks transplantation. This study demonstrated that we developed the 3D induction approach that could efficiently promote the hematopoietic differentiation of mPSCs in vitro and obtained the multipotential progenitors that possessed the short‐term engraftment potential. Abstract : Self‐assembling peptide hydrogel serves as a recapitulation of embryonic development in vitro to a degree of complexity not achievable in a two dimension culture system, We obtained the hematopoietic progenitor cells from pluripotent stem cells in vitro using the self‐assembling peptide hydrogel.